MODERN TEACHING MEDIA IN TEACHING PLANT PHYSIOLOGY - Arzimurodova , Muqaddas (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This methodology is designed for the effective use of virtual technologies in biology education and is based on a practical approach. These methods were developed to create interactive and experimental opportunities for students, to explain biological processes in a demonstrative manner, and to facilitate the learning process. The main goal in biology education is to form an interactive and virtual learning environment, to encourage students to study biological processes, and to organize education through virtual technologies in an interesting, convenient, and practical way.